Identification, Prevalence, and Degree of Digestive Tract Protozoa Infection in Dairy Cows at KUTT Suka Makmur Grati Pasuruan - Margaretha, Josephira Intan; Hastutiek, Poedji; Permatasari, Dian Ayu; Sunarso, Agus; Rahardjo, Dadik; Suwanti, Lucia Tri (Journal of Parasite Science, 2024)
The aim of this research is to identify, determine prevalence, and degree infection of protozoa gastrointestinal tract in dairy cow at KUTT Suka Makmur, Pasuruan district. The research was conducted from July until September 2023 by taking 100 dairy cow faeces sample from 4 villages of KUTT Suka Makmur. The samples were examined by sedimentation and floating methods. Species are identified by looking at morphology of protozoa gastrointestinal. There were of 85 (85%) samples positively infected with protozoan. There were 3 species that infect the digestive tract, those are Eimeria sp., Balantidium sp., and Blastocystis sp. The highest infection of protozoa in this research was Balantidium sp. (54%) followed by Eimeria sp. (47%). In this study, we found that 54 samples (54%) infected by one kind of protozoa and 31 samples (31%) infected by mixed protozoa. The result of Chi Square showed no significant difference in the age on the prevalence of digestive tract protozoa. The result of Kruskal Wallis showed no significant difference in the age and degree infection of Eimeria sp.